Dampak Pembelajaran Sosial Emosional Terhadap Perkembangan Peserta Didik - Vivin Hermawati; Mashudi Mashudi; Mundir Rosyidi; Moh Sahlan (EDUSHOPIA : Journal of Progressive Pedagogy, 2025)
Education is an urgent matter in human life. The essence of education itself is the formation of a person's personality or character. Because education is not only a place to transfer knowledge, but education includes the development of students in various aspects. One of them is the development of social and emotional aspects. In terms of this development, it really needs the guidance of an educator to develop their social and emotional skills. This study uses a literature approach method by reviewing various references on social emotional learning. The results of this study indicate that: Social emotional learning aims to train students' social emotional competencies so that a balance is achieved between academic and social emotional competencies. Integrating social emotional learning with the curriculum is an important step in developing holistic individuals. Social emotional learning has a good impact on the development of students' character, with changes in character, their academic results also increase.